Gabapentin Treatment for Neuropathic Pain in a Child with Sciatic Nerve Injury - Halil Ekrem Akkurt; Haluk Gümüş; Hamit Göksu; Ömer Faruk Odabaşı; Halim Yılmaz (Case Reports in Medicine)
There are a restricted number of studies about usage of gabapentin for neuropathic pain treatment of pediatric patients. We shared a 12-year-old male case with severe neuropathic pain that hindered the rehabilitation programme for the loss of muscle power and movement limitation. Neuropathic pain developed after peripheral sciatic damage due to firearm traumatisation did not respond to other medical treatments but healed nearly completely after gabapentin usage.